2017
DOI: 10.1098/rstb.2016.0101
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling auditory attention

Abstract: Sounds in everyday life seldom appear in isolation. Both humans and machines are constantly flooded with a cacophony of sounds that need to be sorted through and scoured for relevant information—a phenomenon referred to as the ‘cocktail party problem’. A key component in parsing acoustic scenes is the role of attention, which mediates perception and behaviour by focusing both sensory and cognitive resources on pertinent information in the stimulus space. The current article provides a review of modelling studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 87 publications
3
101
0
2
Order By: Relevance
“…This promises new insight on the much-debated delineation of functional sub-regions of auditory cortex and adds to the demonstrated utility of neural networks in parcellating not only speech but also the gist of auditory scenes (e.g. [46]). Fortunately, excellent software toolboxes to aid in DNN training are readily available [47,48].…”
Section: A Tripartite Approach To Tackle Current Methodological Challmentioning
confidence: 99%
“…This promises new insight on the much-debated delineation of functional sub-regions of auditory cortex and adds to the demonstrated utility of neural networks in parcellating not only speech but also the gist of auditory scenes (e.g. [46]). Fortunately, excellent software toolboxes to aid in DNN training are readily available [47,48].…”
Section: A Tripartite Approach To Tackle Current Methodological Challmentioning
confidence: 99%
“…Similar to how ‘colour’ is used to compute salience in the visual modality, Southwell et al [6] have found that one salient property of auditory stimuli is ‘predictable repetition over time’ . For a broader background, this issue also includes comprehensive review comparing models of auditory and visual salience [7]. …”
Section: Visual Scene Analysis In the Brainmentioning
confidence: 99%
“…In turn, theoretical frameworks developed to model empirical data remain limited in scope and fail to generalize beyond the contexts for which they were developed. 14 The current study aims to break this barrier and offer a baseline database for auditory salience from an unconstrained choice of stimuli. This collection includes a variety of complex natural scenes, which were selected with a goal of representing as many types of real world scenarios as possible.…”
mentioning
confidence: 99%